Crosstalk between ubiquitination and translation in neurodevelopmental disorders - Elu, Nagore; Subash, Srividya; R. Louros, Susana (Frontiers in Molecular Neuroscience, 2024)
Ubiquitination is one of the most conserved post-translational modifications and together with mRNA translation contributes to cellular protein homeostasis (proteostasis). Temporal and spatial regulation of proteostasis is particularly important during synaptic plasticity, when translation of specific mRNAs requires tight regulation. Mutations in genes encoding regulators of mRNA translation and in ubiquitin ligases have been associated with several neurodevelopmental disorders. RNA metabolism and translation are regulated by RNA-binding proteins, critical for the spatial and temporal control of translation in neurons. Several ubiquitin ligases also regulate RNA-dependent mechanisms in neurons, with numerous ubiquitination events described in splicing factors and ribosomal proteins. Here we will explore how ubiquitination regulates translation in neurons, from RNA biogenesis to alternative splicing and how dysregulation of ubiquitin signaling can be the underlying cause of pathology in neurodevelopmental disorders, such as Fragile X syndrome. Finally we propose that targeting ubiquitin signaling is an attractive novel therapeutic strategy for neurodevelopmental disorders where mRNA translation and ubiquitin signaling are disrupted.